Interplay between innate immunity and the viral oncoproteins Tax and HBZ in the pathogenesis and therapeutic response of HTLV-1 associated adult T cell leukemia - El Hajj, Hiba; Bazarbachi, Ali (Frontiers in Immunology, 2022)
The Human T-cell Leukemia virus type 1 (HTLV-1) causes an array of pathologies, the most aggressive of which is adult T-cell leukemia (ATL), a fatal blood malignancy with dismal prognosis. The progression of these diseases is partly ascribed to the failure of the immune system in controlling the spread of virally infected cells. HTLV-1 infected subjects, whether asymptomatic carriers or symptomatic patients are prone to opportunistic infections. An increasing body of literature emphasizes the interplay between HTLV-1, its associated pathologies, and the pivotal role of the host innate and adoptive immune system, in shaping the progression of HTLV-1 associated diseases and their response to therapy. In this review, we will describe the modalities adopted by the malignant ATL cells to subvert the host innate immune response with emphasis on the role of the two viral oncoproteins Tax and HBZ in this process. We will also provide a comprehensive overview on the function of innate immunity in the therapeutic response to chemotherapy, anti-viral or targeted therapies in the pre-clinical and clinical settings.